The Trusts: Facts Established and Problems Unsolved - Jenks, Jeremiah W. (Quarterly Journal of Economics, 1900)
Journal Article The Trusts: Facts Established and Problems Unsolved Get access Jeremiah W. Jenks Jeremiah W. Jenks Cornell University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 15, Issue 1, November 1900, Pages 46–74, https://doi.org/10.2307/1885861 Published: 01 November 1900